Relationship of stigmatisation degree, selfesteem and knowledge of asthma with asthma control and independent variables from socio-demographic and medical data in adult asthma patients / Sohail Ahmad - Ahmad, Sohail (2016)
The control of asthma is influenced by psychosocial wellbeing and socio-demographic and medical characteristics of adult asthma patients. The main objectives of this present study were to determine the reliability and validity of translated Malaysian version of stigmatisation degree, self-esteem and knowledge (M-SDSE-K) of asthma instrument in adult asthma patients, to assess the level of stigmatisation degree (SD), self-esteem (SE), knowledge and control of asthma (AC), to investigate the differences of SDSE-K of asthma and AC among independent variable categories and to examine the relationship of SDSE-K of asthma and AC with independent variables from patients' socio-demographic and medical data and among respective dependent variables. In this cross-sectional study, adult asthma patients were recruited for pilot (n = 30) and main (n = 152) studies using purposive sampling method. The study was conducted in multiple respiratory clinics in Selangor, Malaysia. The M-SDSE-K of asthma instrument was found to be valid and reliable by both Modern Response Theory (MRT) and Classical Test Theory (CTT). The enrolled asthma patients possessed moderate level of SD, moderate level of SE, and good level of knowledge of asthma. No statistically significant association was found between independent study variables with SDSE-K of asthma and AC, except with four variables of occupation, number of years since diagnosed as asthmatic, hospitalisation and emergency visits for AC. Furthermore, AC showed significant negative correlation with number of hospitalisations, number of emergency visits and number of asthma triggers as mentioned by the patients. For SD, emergency visits of the asthma patients showed significant weak positive correlation. Patients' knowledge of asthma was significant weak negatively correlated with number of years diagnosed as asthmatic. Moreover, AC showed moderately significant negative correlation with SD, and significant weak positive correlation with SE. The findings of multiple linear regression analysis showed that the number of patients' visits to emergency department because of asthma was the significant predictor to level of AC among all selected study variables from sociodemographic and medical data. From dependent variables, SD and SE of asthma patients were the significant predictors to AC. The asthma patients' emergency visits and patients' level of education were the significant predictors for SD. For SE and knowledge of asthma, no predictor was detected out of all selected variables. The findings of both multinomial logistic regression and binary logistic regression suggested that only the patients' age was a significant predictor for AC in both studied regression models for SDSE-K of asthma and AC. The selected study variables from socio-demographic and medical data; for SD: the patients' highest completed level of education and number of years since diagnosed as asthmatic; for SE: none of the variables; for knowledge: the number of years since diagnosed as asthmatic; and for AC: patients' age, showed significant effect on SD, SE, knowledge and control of asthma. The evidences presented in this study supported the fact that numerous factors such as socio-demographic and medical factors are capable of influencing asthma control as well as psychosocial wellbeing of the asthma patients.